대장암의 유전병인 - 김진천(Jin Cheon Kim) (Annals of surgical treatment and research, 2005)
Cancer occurs from the functional derangements of complex genomic structure. Colorectal carcinogenesis, from hereditary colorectal cancers, has been widely investigated by excavating their related genes. Colorectal carcinogenesis is significantly implicated with alterations of APC and mismatch repair genes, causative genes for familial adenomatous polyposis (FAP) and hereditary nonpolyposis colorectal cancer (HNPCC), respectively, along the entire stages. The functional loss of APC and mismatch repair proteins appears to affect various biological processes, i.e. cell cycle, apoptosis, and cellular signaling pathways including receptor protein tyrosine kinase, Wnt/cadherin and TGFβ, which determine various tumor phenotypes. These genomic changes provide different penetrance of cancer risk according to the related genes. The classical Vogelstein pathway starting from APC mutation is comprised of a stepwise or consecutive model in colorectal carcinogenesis. Although this model explains genopathogenesis in a simplified way, numerous genomic changes in vivo occurr selectively or accumulatively. This model was thereby consistent in less than 10% of all colorectal cancers. Alternatively, the nexus pathway stochastically implies complex connections between respective genes that elucidate various phenotypes. Colorectal genopathogenesis has not been well documented with respect to explaining the diverse clinicopathological manifestations regardless of the recent advances in genomic technology. Various categories of colorectal carcinogenesis are arranged and reviewed in regard to their genetic penetrance, related-gene mutations and their interactions, epigenetic changes, and chromosomal alterations. KCI Citation Count: 4